Research Question : How do AI-Based Decision Support Systems Influence Managerial Decision-Making Processes in Businesses? - Risha Sheth (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
According to research by Oracle and Seth Stephens-Davidowitz, 85% of business leaders have experienced decision stress, and three-quarters have seen the daily volume of decisions they need to make increase tenfold over the last three years. As businesses keep growing rapidly, competition becomes tougher. Consequently, business leaders and managers are facing increasing pressures to come up with the right decisions for their business. In cases where vast amounts of data needs to be analyzed, there resides a high chance of patterns and information going unnoticed by humans. Consequently, Poor decision making is estimated to cost firms on average at least 3% of profits, which for a 5 billion company amounts to a loss of around 150 million each year. This may affect a likely business’ finances to a huge extent. Furthermore, analyzing such vast amounts of data is inefficient in relation to time and productivity. Consequently, This process also hinders business teams’ concentration on tasks aligned with their expertise.